Perceived barriers for accessing international research funding among Latin American researchers - Jesica Formoso; Paz Miguez; Nicolás Palopoli; Irene Vazano; Julián Buede; Juan Pablo Barreyro; Laura Ación (PLoS ONE, 2026)
Access to international funding is increasingly essential for sustaining research in a highly competitive and globalized scientific landscape; however, researchers in Latin America face persistent structural constraints that limit their competitiveness. This study aimed to identify perceived barriers and strategies to mitigate structural disadvantages in accessing international research funding. We employed a sequential mixed-methods design. In the qualitative phase, a virtual focus group with five researchers from Mexico, Colombia, Argentina, and Guatemala explored experiences with international grant applications. Thematic analysis revealed three overarching themes: (1) strategies and good practices; (2) barriers and structural constraints; and (3) recommendations to support more inclusive funding practices. Barriers included language and cultural differences, perceived bias from Global North funders, differences in infrastructural expectations, and limited opportunities for networking. These insights informed the design of a quantitative survey, which was completed by 253 researchers from 16 countries; 60.4% had applied to international calls and 43.6% reported receiving at least one grant. Across 668 reported applications, success rate was 40.6%. The most frequently endorsed barriers were economic costs of networking (92.3%), misalignment between eligibility criteria and local trajectories (80.8%), rhetorical differences in grant writing (75.3%), and self-perceptions of lower competitiveness (69.2%). Results highlight persistent structural, linguistic, and cultural barriers that shape access to international funding. Participants proposed actionable strategies—particularly for international funders seeking to broaden Global South participation—including context-sensitive grant-writing training, mentorship schemes, and funding calls explicitly designed to account for the Latin American realities.